The Voyage of the "Discovery" Vol. I. - Scott, Robert F. (Smith, Elder & Co., London, 1905)
In two volumes. With 260 full-page and smaller illustrations by Dr. E. A. Wilson and other members of the expedition, photogravure frontispieces, 12 coloured plates in facsimile from Dr. Wilson's sketches, panoramas and maps.